Organizational turnaround: moving beyond one-size-fits-all solutions. Issue 3 (3rd May 2020) - Rutherford, Amanda; Favero, Nathan
Abstract: Literature on organizational turnaround has frequently suggested, but rarely investigated, the possibility that turnaround strategies for failing organizations must be matched to the specific needs of the organization. Building on work related to causes of decline in private sector literature, this study offers a framework for matching strategic interventions to the current state of an organization's functioning in terms of resources (material and human), coordination (horizontal and vertical), and the environment. Using a panel dataset of New York City schools, we find that two understandings of turnaround that often appear mutually exclusive—that an organization can improve performance by shoring up weaknesses and that an organization should play to its current strengths—can complement each other and may both appropriately describe different types of organizational challenges.